A experiência de mães de crianças com diagnóstico de autismo nível II ou III: uma compreensão fenomenológica. - Falcão, Christianne Andrea Müller Marinho (2024)
Mothers caring for an autistic child often find themselves in situations where they are perceived, not infrequently, as atypical mothers, including in my practice, where I work with mothers of children and teenagers diagnosed with Autism. In this context, I question what constitutes this understanding of atypical motherhood and how it manifests. From an existential perspective, this dissertation aims to understand the experience of mothers with children diagnosed with Level II or III Autism, seeking to explore the meaning of motherhood in today's context. It reflects on the concept of atypical motherhood, discusses the understanding of autism considering the health/illness debate framed by Hermeneutic Phenomenology, and analyzes the experiences of women-mothers of these children. The narrative interviews with the participants were guided by the question: "What is your experience of motherhood with your child?". I also recorded my own narratives in my research diary. As a comprehensive framework for interpretation, I adopted directions opened by Philosophical Hermeneutics, which sees research as the possibility of weaving a conversation and the horizon revealed in this dialogue as a "fusion of horizons," uncovered in a comprehensive play. The narrated experiences are unique but converge in the fear of dying and leaving the child unprotected, as well as in the hope for the child's development. In the end, the insights gained throughout the research allowed for an expansion of the meaning of these experiences beyond the biomedical model and will contribute to reflections for the practice of health professionals working with mothers (families) of autistic children, including psychologists.